2020
DOI: 10.3310/hta24130
|View full text |Cite
|
Sign up to set email alerts
|

Surgical interventions for uterine prolapse and for vault prolapse: the two VUE RCTs

Abstract: Background New surgical approaches for apical prolapse have gradually been introduced, with few prospective randomised controlled trial data to evaluate their safety and efficacy compared with traditional methods. Objective To compare surgical uterine preservation with vaginal hysterectomy in women with uterine prolapse and abdominal procedures with vaginal procedures in women with vault prolapse in terms of clinical effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 79 publications
3
20
0
Order By: Relevance
“…Our ndings concur with other groups, [14,27,28], where we demonstrated that the issues of the impact of a hysterectomy on femininity, sex drive and sexual satisfaction, either for the woman or her partner, did not seem to be a priority in the decision-making process regarding hysterectomy at time of POP surgery. However, the impact of hysterectomy on clinical outcomes seemed to be an important factor when choosing the optimal procedure.…”
Section: Discussionsupporting
confidence: 90%
“…Our ndings concur with other groups, [14,27,28], where we demonstrated that the issues of the impact of a hysterectomy on femininity, sex drive and sexual satisfaction, either for the woman or her partner, did not seem to be a priority in the decision-making process regarding hysterectomy at time of POP surgery. However, the impact of hysterectomy on clinical outcomes seemed to be an important factor when choosing the optimal procedure.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to those of Korbly et al [14] and van IJsselmuiden et al [17] the number of women opting for uterine sparing surgery in our study signi cantly reduced if this was associated with slightly inferior anatomical outcomes (34.4% to 8.8 %; OR 11.6, p<.001). A large RCT comparing uterine preservation surgery versus vaginal hysterectomy for POP repair reported similar anatomical and functional outcomes at 12-months [29]. In our survey sacrocolpopexy was the most preferred surgical procedure amongst female gynecologists.…”
Section: Discussionmentioning
confidence: 51%
“…Similar to those of Korbly et al [ 14 ] and van IJsselmuiden et al [ 17 ] the number of women opting for uterine sparing surgery in our study significantly reduced if this was associated with slightly inferior anatomical outcomes (34.4–8.8%; OR 11.6, p < 0.001). A large RCT comparing uterine preservation surgery versus vaginal hysterectomy for POP repair reported similar anatomical and functional outcomes at 12-months [ 29 ]. In our survey sacrocolpopexy was the most preferred surgical procedure amongst female gynecologists.…”
Section: Discussionmentioning
confidence: 99%